2006
DOI: 10.5194/hess-10-981-2006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical process upscaling for deriving catchment scale state variables and constitutive relations for meso-scale process models

Abstract: Abstract. In this study we propose an uspcaling approach to derive time series of (a) REW scale state variables, and (b) effective REW scale soil hydraulic functions to test and parameterise models based on the REW approach. To this end we employed a physically based hydrological model, that represents the typical patterns and structures in the study catchment, and has previously been shown to reproduce observed runoff response and state dynamics well. This landscapeand process-compatible model is used to simu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 29 publications
1
68
0
Order By: Relevance
“…We suggest that the REW approach (Reggiani et al, 1998(Reggiani et al, , 1999(Reggiani et al, , 2000Reggiani and Rientjes, 2005) already meets the second requirement (Lee et al, 2005(Lee et al, , 2007Zehe et al, 2005bZehe et al, , 2006Zhang et al, , 2006Beven, 2006), however, it fails to meet the first. Furthermore, it is a suitable framework to reunify the different fields of hydrological research as it postulates the existence of functional units with homogeneous hydrological response/behaviour in the landscape (Beven, 2006;.…”
Section: Future Models Based On Observables and Landscape Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that the REW approach (Reggiani et al, 1998(Reggiani et al, , 1999(Reggiani et al, , 2000Reggiani and Rientjes, 2005) already meets the second requirement (Lee et al, 2005(Lee et al, , 2007Zehe et al, 2005bZehe et al, , 2006Zhang et al, , 2006Beven, 2006), however, it fails to meet the first. Furthermore, it is a suitable framework to reunify the different fields of hydrological research as it postulates the existence of functional units with homogeneous hydrological response/behaviour in the landscape (Beven, 2006;.…”
Section: Future Models Based On Observables and Landscape Structuresmentioning
confidence: 99%
“…In a modelling study Zehe et al ( , 2006 showed that a reduced population of earthworms that goes along with a reduction of apparent connected preferential pathways would thus reduce the intensity threshold for overland flow production and increase connectivity of surface flow paths that control overland and thus flood response. A positive effect of an apparently lower number of earthworms and thus worm burrows would be a lower susceptibility for rapid transport of agrochemicals and thus a possible reduction of related environmental risk.…”
Section: Biological Controls Of Hydrological Functioning In Pristine mentioning
confidence: 99%
“…In contrast to what the terms imply, different applications of fully distributed models span several magnitudes of grid sizes from centimetres to kilometres (e.g. Butts et al, 2004;Kollet and Maxwell, 2006;Zehe et al, 2006;Kumar et al, 2013), and thus do not necessarily describe the system at a higher spatial resolution than so-called semi-distributed models, as the applied grid cells can often be larger than sub-catchments and/or hydrological response units (e.g. Nijzink et al, 2016a).…”
Section: Spatially Distributed Modelsmentioning
confidence: 99%
“…Zehe et al, 2007) caused by the combined effects of limited observation accuracy and representativeness.…”
Section: Modelling Myths -Or Not?mentioning
confidence: 99%
See 1 more Smart Citation